2019
DOI: 10.2196/12997
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Professions Education on Diabetes Management: Systematic Review by the Digital Health Education Collaboration

Abstract: Background There is a shortage of health care professionals competent in diabetes management worldwide. Digital education is increasingly used in educating health professionals on diabetes. Digital diabetes self-management education for patients has been shown to improve patients’ knowledge and outcomes. However, the effectiveness of digital education on diabetes management for health care professionals is still unknown. Objective The objective of this study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…We are also aware of recent reviews, which reached similar conclusions [55-62]. For example, digital education seems to be at least as effective (and sometimes more effective) as traditional education in improving dermatology, diabetes management, or smoking cessation–related skills and knowledge [58,61,62]. Most of these reviews, however, stressed the inconclusiveness of overall findings mainly because of the low certainty of the evidence.…”
Section: Discussionmentioning
confidence: 85%
“…We are also aware of recent reviews, which reached similar conclusions [55-62]. For example, digital education seems to be at least as effective (and sometimes more effective) as traditional education in improving dermatology, diabetes management, or smoking cessation–related skills and knowledge [58,61,62]. Most of these reviews, however, stressed the inconclusiveness of overall findings mainly because of the low certainty of the evidence.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, we adopted alternative approaches to literature synthesis, keeping in mind the needs of various stakeholders in health professions education [34]. We have focused our evidence synthesis on digital education for a specific topic or condition (eg, smoking cessation [20], diabetes [21], domestic violence, and antibiotic management), discipline (eg, dermatology [10], pediatrics, geriatrics, leadership, and management [14]), roles of health professionals (eg, medical doctors [18], medical students [17], and preregistration [undergraduate] and postregistration [postgraduate] health professionals [11]), pedagogical foundations with relevant technology applications (eg, digital problem-based learning [35]), and type of outcome (eg, cognitive skills such as communication or diagnostic skills) [12].…”
Section: Defining the Scopementioning
confidence: 99%
“…We attempted to explore possible clinical or methodological reasons for this variation by performing prespecified subgroup analysis. In most reviews, high heterogeneity precluded statistical pooling [10-12,20,21], and prespecified subgroup analyses did not provide an explanation for the observed heterogeneity. In such cases, we performed a narrative synthesis of findings.…”
Section: Assessment Of Heterogeneitymentioning
confidence: 99%
“…4 In another systematic review of 12 studies (1990-2017), digital education was found to be more effective than traditional education to enhance knowledge and skills for diabetes management. 5 However, the low quality of these studies makes it difficult to formulate firm conclusions.…”
Section: Introductionmentioning
confidence: 99%